Peran Komunikasi dengan Orang Tua dan Perilaku Seksual Remaja: Studi Metaanalisis - Widyarini, Nurlaela; Retnowati, Sofia; Setiyawati, Diana (Jurnal Ilmu Keluarga dan Konsumen, 2019)
Previous research on parent-adolescent communication and adolescent sexual behavior showed some inconsistent results. A meta-analysis was performed for the purpose of determining the magnitude of association between parent-adolescent communication and adolescent’s sexual behavior. Adolescent’s sexual behavior encapsulates knowledge about sexual and reproductive health (healthy sexual behavior, reproductive health and risky sexual behavior), attitude on sexuality, intention and sexual behavior (dating, intercourse and pregnancy), self efficacy and sel control in abstinence and condom use. This study is conducted by analysis of scientific articles from EBSCO, ProQuest, Science Direct, Taylor & Francis, Willey, and Sage Publication. The study selected studies published from 2001-2015 that were written in English. The participants of the studies had age ranged from 10-24 years, based on WHO definition of young people. Based on inclusion criteria, the initial searched yielded 121 articles, 20 articles with 55 studies of which were eligible. The results of the meta-analysis showed that parent-adolescent communication determined adolescent sexual behavior (r=0,08). Meanwhile, communication has more significant influence on adolescent’s sexual behavior based on parent perceived (r=0,62) compared with perceived by adolescents (0,43) or adolescents-parents (0,48). Future studies based on the limitations are needed for further understanding the effect of parent-adolescent communication in term of sexuality regarding on culture and gender differences.